230k views
5 votes
Use substitution to solve the system. x=2y+5 2x-5y=11

2 Answers

5 votes

Answer:

(3, - 1 )

Explanation:

Given the 2 equations

x = 2y + 5 → (1)

2x - 5y = 11 → (2)

Substitute x = 2y + 5 into (2)

2(2y + 5) - 5y = 11 ← distribute and simplify left side

4y + 10 - 5y = 11

10 - y = 11 ( subtract 10 from both sides )

- y = 1 ( multiply both sides by - 1 )

y = - 1

Substitute y = - 1 into (1) for corresponding value of x

x = 2(- 1) + 5 = - 2 + 5 = 3

Solution is (3, - 1 )

5 votes

Answer:

Solve for the first variable in one of the equations, then substitute the result into the other equation.

Point Form: ( 3 , − 1 )

Equation Form: x = 3 , y = − 1

(I hope it helps ♡^▽^♡)

User Bruno Antunes
by
5.2k points